2009
DOI: 10.1124/jpet.109.161109
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Suppression of Experimental Autoimmune Encephalomyelitis by a Novel Bifunctional Peptide Inhibitor: Structure Optimization and Pharmacokinetics

Abstract: The objective of this study was to optimize the in vivo activity of proteolipid protein (PLP)-bifunctional peptide inhibitor (BPI) molecule to suppress experimental autoimmune encephalomyelitis (EAE) in SJL/J mice and evaluate pharmacokinetic profiles of PLP-BPI. PLP-BPI is constructed via conjugation of myelin PLP 139-151 with CD11a 237-246 -derived peptide (LABL) via a spacer. The hypothesis is that PLP-BPI binds simultaneously to major histocompatibility complex-II and intercellular adhesion molecule-1 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…Previously, a bifunctional peptide inhibitor (BPI) demonstrated the importance of co-delivering both antigenic peptide and a peptide inhibiting T cell activation by blocking immune cell adhesion (22,23,(26)(27)(28). Applying this codelivery approach of autoantigen and peptide inhibitor to a multivalent delivery vehicle (SAgA PLP:LABL ), i.e., multiple copies of peptide per therapeutic molecule, has also suppressed EAE (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, a bifunctional peptide inhibitor (BPI) demonstrated the importance of co-delivering both antigenic peptide and a peptide inhibiting T cell activation by blocking immune cell adhesion (22,23,(26)(27)(28). Applying this codelivery approach of autoantigen and peptide inhibitor to a multivalent delivery vehicle (SAgA PLP:LABL ), i.e., multiple copies of peptide per therapeutic molecule, has also suppressed EAE (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of antigen specificity to such an approach may reduce undesired side effects associated with global immunosuppression that accompanies many of the current immunomodulatory therapies available (4-7). Indeed, several groups have begun investigating antigen-specific immunotherapies to treat autoimmune disorders (22)(23)(24)(25)(26)(27)(28)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EAE is an animal model for multiple sclerosis (MS). PLP-BPI derivatives are able to suppress EAE better than the parent PLP peptide (PLP 139-151 ), indicating that the presence of LABL peptide alters the mechanisms of action of PLP-BPI compared to PLP peptide alone (Kobayashi et al, 2008;Kobayashi et al, 2007;Ridwan et al, 2010;Zhao et al, 2010). Cytokine studies indicated that PLP-BPI treatment induced the differentiation and proliferation of T-reg and Th2 cells and suppressed the proliferation of Th17 cells.…”
Section: Design Of Novel Gad-bpi For Suppressing T1dmentioning
confidence: 99%
“…Using the distance estimate, a combination of glycine (G) and amino caproic acid (Acp) was used to connect LABL to GAD peptides. In general, BPI molecules are effective in suppressing different autoimmune diseases; for example, GAD-BPI, PLP-BPI, and CII-BPI molecules (Table 1) have excellent efficacy to suppress T1D (Murray et al, 2007), EAE (Kobayashi et al, 2008;Kobayashi et al, 2007;Ridwan et al, 2010;Zhao et al, 2010), and RA, respectively. The central hypothesis is that binding of BPI molecules simultaneously to MHC-II and ICAM-1 on the surface of APC blocks the immunological synapse formation at the interface of APC-T cells.…”
Section: Design Of Novel Gad-bpi For Suppressing T1dmentioning
confidence: 99%